Bootstrap panel granger-causality between government budget and external deficits for the EU - António Afonso; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2009)
We investigate the existence of Granger-causality between current account and government budget balances over the period 1970-2007, for different EU and OECD country groupings. We use the panel-data approach of Kónya (2006), which is based on SUR systems and Wald tests with country specific bootstrap critical values. Our results show a causal relation from budget deficits to current account deficits for several EU countries: Bulgaria, Czech Republic, Estonia, Finland, France, Italy, Hungary, Lithuania, Poland, and Slovakia, along the lines of the so-called twin-deficit relationship. Considering the effective real exchange rate in the SUR system does not substantially alter the results.
Keywords: C23; E62; F32; H62; 330; Panel causality tests; budget deficit; external imbalance; real exchange rates; EU; OECD; Haushaltsdefizit; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Kaufkraftparität; Kausalanalyse; Panel; Schätzung; EU-Staaten; OECD-Staaten